Efektivitas Penggunaan Media Pembelajaran CardBoard Box Dalam Mengevaluasi Pemahaman Nahwu di MTs Ittihadul Ummah - Amalia Rahajeng Wulandari; Suparmanto; Muhammad Walid; Nisrina Qatrun Nada (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2023)
This study aims to determine how effective the card board box learning media is in knowing and evaluating students' understanding of nahwu subject matter. This research uses quantitative methods. The results of our research regarding the effectiveness of cardboard box learning media for students of MTs Ittihadil Ummah grade 8, totaling 8 students consisting of 4 female students and 4 male students, were unsatisfactory, many of the students did not understand the qowaid material presented, as well as the definition of the material. contained in the cardboard box learning media does not function optimally. One in four female students has good abilities in understanding lessons and using media. While all male students are active in learning. One male student has good abilities and the other is quite good.